Comparing Effects of Intrinsic and Extrinsic Social Values Between Younger and Older Employees. Issue 6 (17th August 2016) - Yeung, Dannii Y.; Fung, Helene H.; Chan, Darius K.-S.
ABSTRACT: Socioemotional selectivity theory proposes that older adults emphasize emotional goals and interpersonal closeness to a greater extent than do younger adults, suggesting that holding social work-related values (SWVs) may be beneficial to older employees. This project aimed at examining two dimensions of SWVs, intrinsic and extrinsic SWVs, and tested whether age and work situation would moderate their effects on self-rated job performance. A cross-sectional survey (Study 1, N = 357) and a 14-day experience sampling study (Study 2, N = 77) were conducted among Chinese managerial employees. Study 1 showed that the direct effect of intrinsic SWVs on self-rated job performance was stronger in older employees than in younger employees. Study 2 demonstrated that older employees who valued intrinsic SWVs while being in social situations performed much better than when they did not value intrinsic SWVs but being in social situations; however such positive effect was not shown in younger employees. Findings of this project reveal that the effect of SWVs varies across locus of effect (intrinsic versus extrinsic), age, and work situation. Among older employees, the positive effect of intrinsic SWVs is more crucial than that of extrinsic SWVs on self-rated job performance. Findings of this project imply that intrinsically rewarding incentives would be more effective in motivating older employees to reach peak performance.